(untitled) (Bangladesh Journal of Agricultural Research, 2017)
There is a common perception among farmers and concerned professionals that maize grain cannot be stored like paddy or other cereals in conventional rural storage devices. As such, farmers generally sell their produce at harvest for any price offered to avoid quality deterioration and losing total return after harvest, which leads to lower profitability. To counter this situation, in the recent years, some progressive farmers at Chuadanga district (one of the concentrated maize growing area of Bangladesh) have been storing their maize grain within their household by using traditional bamboo granaries (Golas in the Bengali language) with the aim to capture higher future prices, while these Golas are traditionally used for storing paddy. Through the Cereal Systems Initiative for South Asia in Bangladesh (CSISA-BD) project, the International Maize and Wheat Improvement Center (CIMMYT) also helps further more to disseminate this technologies in the Chuadanga area. Given the uptake of this profitincreasing strategy by farmers, it is essential to document and evaluate the knowledge learned in order to inform scale-out efforts designed to reach farmers in other areas. A survey was conducted to assess maize grain storage systems in use at the household level in Chuadanga District farmers, and to estimate the overall profitability of storing maize grain. The survey results showed that approximately 80% of the total maize grain produced in 2014 (5.93 t/ha, on average) by sampled farmers was stored; most households employed Gola (62%) and/or jute sacks (55%), among other options. Golas were their first preference, followed by storage systems that pair polythene bags with (respectively) jute sacks and plastic bags, and then several other options. On average, farmers stored their maize grain 25.6 weeks (2014), 21 weeks (2013), and 20.9 weeks (2012) while realizing a price benefit of BDT 2.16/kg, BDT 4.72/kg, and BDT 5.35/kg in the respective years. Despite the fact that average storage costs and average quantities stored both varied by less than 7% between 2012 and 2014, the profit per unit (100 kg) and profit per household was significantly less in 2014 (BDT 10,161) than in 2013(BDT 24,445) and 2012 (BDT 30,255), due to the much lower price differential obtained from maize grain storage in 2014. Examination of the total unit cost of storage reveals that the Golas were the most profitable storage system employed by the farmers and its profits helps farmers to improve their livelihood. Proper dissemination of these practices (storing and Gola) could be helpful for the farmers at the intensive maize growing area. Limitation of drying space and higher labour cost were the two major problems faced by the farmers, introducing quick-drying devices (flatbed dryers) can solve both the problems. It can be established either by local service providers, or farmers organizing themselves for collective ownership of such equipment. Bangladesh J. Agril. Res. 42(3): 549-561, September 2017